Preparation of water-permeable bricks derived from fly ash by autoclaving. (15th February 2021) - Li, Jiahao; Li, Xilong; Liang, Sha; Zhang, Yuanshang; Ye, Qiang; Zhang, Li; Pan, Chaoqun; Lv, Ruibin; Li, Qingyi; Xiao, Keke; Yan, Yilei; Chen, Ye; et al.
Graphical abstract: Highlights: Granulated fly ash made by geopolymerization was used as aggregate. The amount of fly ash in the prepared water-permeable bricks was up to 50 wt%. The water permeability of brick was positively related to its connected pores. The pore structures of water-permeable bricks were illustrated by mercury intrusion porosimetry (MIP). Micro computed tomography (Micro-CT) was used to study the pore structures of water-permeable bricks. Abstract: In this study, water-permeable bricks were prepared from fly ash (FA) by autoclaving. Granulated FA prepared by geopolymerization was used as aggregate and mixed with fine FA to achieve a high content of FA (>50 wt%) in water-permeable bricks. Effects of sodium silicate dose, water/fine FA mass ratio, forming pressure and autoclaving time on the performance of water-permeable bricks were investigated. Under optimal conditions, the compressive strength and permeability coefficient of prepared bricks could reach 35.5 MPa, and 1.044 × 10 -4 m/s, respectively. The mineral compositions, micro-morphology, and pore distribution of the permeable bricks were investigated. The pore structure of permeable bricks was investigated by using mercury intrusion porosimetry and micro computed tomography. The connected pores in bricks contribute to the higher water permeability coefficient.